Cytological Diagnosis of Thyroid Diseases: Practical Significance and Modern Approaches - Ergasheva Gulshan Tokhirovna (American Journal of Bioscience and Clinical Integrity, 2025)
Thyroid diseases, particularly nodular and autoimmune conditions, have shown a global rise in prevalence, necessitating accurate, minimally invasive diagnostic approaches. Despite advancements in imaging modalities, many thyroid pathologies share overlapping clinical and sonographic features, limiting the reliability of imaging alone for definitive diagnosis. This article addresses this diagnostic gap by evaluating the clinical importance and methodology of fine-needle aspiration biopsy (FNAB) in the cytological assessment of thyroid disorders. FNAB is emphasized as the gold standard for preoperative diagnosis, enabling precise differentiation between benign and malignant lesions, especially in endemic goiter and iodine-deficient regions. The study outlines FNAB techniques, cytomorphological criteria, and the Bethesda classification system used to interpret cytology results. Findings highlight FNAB’s ability to accurately detect colloid goiter, autoimmune thyroiditis, adenomas, and various carcinomas with high sensitivity. Additionally, integration with ultrasound and hormonal assays significantly improves diagnostic accuracy. The practical implication of this approach lies in guiding surgical decisions, preventing unnecessary operations, and enabling tailored treatment strategies. The results affirm FNAB’s diagnostic value, especially when performed by experienced specialists using optimized methods. Future research should focus on enhancing FNAB interpretation in indeterminate cases and exploring adjunctive molecular diagnostics to further refine cytological assessmentsCytological diagnosis of thyroid diseases plays a crucial role in modern endocrinology. Fine-needle aspiration biopsy (FNAB) offers high accuracy in verifying nodular formations, tumors, and autoimmune conditions, particularly in early stages. This article explores the methodology of specimen collection, cytomorphological criteria for evaluating cell samples, and the diagnostic value of this method in clinical decision-making.